STUDI KARAKTERISTIK TANAH HUTAN BAKAU DI AREAL LAHAN BASAH KOTA BONTANG - Makhrawie . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
A study that aimed to identify characteristics of mangrove forest soil and their inter-relationships, and to know status and limiting factor of the soil fertility, was conducted at wetland area around Badak NGL Company, Bontang City, Province of East Kalimantan. Results of the study showed that there was 2 main great groups of soil, tropofluvents and tropopsamments. Great group tropfluvents at Zone I and II of mangrove forest area is characterized by fibric, silty loam until loam texture, no until slightly clay and until moderately plastic consistency, with soil colour varied in black, brownish black, very dark brown, brown until brownish grey. At while great group tropopsamments which located at pulau  Siaca (SCK) is characterized by sand and sandy texture, no clay and no plastic consistency with soilcolour was light grey dominantly. Salinity of soil was positively related to content of sulphate (r = 0.55), while pH H2O was negatively related to soluble sulphate (r=0.62). Soil cation exchange capacity (CEC) was also negatively related to exchangeable sodium percentage (ESP) (r=0.93). Hight content of soil sulphate was found at location of 25 Ha-mangrove forest, Sekambing Baltim and Sekambing Muara. Hight Sodium Absorption Ratio (SAR) was found at Sekangat and Sekambing Muara. Most of observation areas indicated hight to very hight status of soil fertility, except location of 25 ha-mangrove forest (L25 M and L 25 H) that indivated was low soil status and pulau Siaca (SCK) was moderately soil status. These low to moderately soil fertility status was determined by very low Phosphore, as main soil limiting factor.